Review of orthopaedic trauma surgery during the peak of COVID-19 pandemic – An observational cohort study in the UK - De, Chiranjit (J Clin Orthop Trauma, 2021)
AIM: This study aims to estimate the risk of acquiring medical complication or death from COVID-19 infection in patients who were admitted for orthopaedic trauma surgery during the peak and plateau of pandemic. Unlike other recently published studies, where patient-cohort included a more morbid group and cancer surgeries, we report on a group of patients who had limb surgery and were more akin to elective orthopaedic surgery. METHODS: The study included 214 patients who underwent orthopaedic trauma surgeries in the hospital between 12th March and 12th May-2020 when the pandemic was on the rise in the United Kingdom. Data was collected on demographic profile including comorbidities, ASA grade, COVID-19 testing, type of procedures and any readmissions, complications or mortality due to COVID-19. RESULTS: There were 7.9% readmissions and 52.9% of it was for respiratory complications. Only one patient had positive COVID-19 test during readmission. 30-day mortality for trauma surgeries was 0% if hip fractures were excluded and 2.8% in all patients. All the mortalities were for proximal femur fracture surgeries and between ASA Grade 3 and 4 or in patients above the age of 70 years. CONCLUSION: This study suggests that presence of COVID-19 virus in the community and hospital did not adversely affect the outcome of orthopaedic trauma surgeries or lead to excess mortality or readmissions in patients undergoing limb trauma surgery. The findings also support resumption of elective orthopaedic surgeries with appropriate risk stratification, patient optimization and with adequate infrastructural support amidst the recovery phase of the pandemic.